Repeated electroacupuncture treatment attenuated hyperalgesia through suppression of spinal glial activation in chronic neuropathic pain rats - Jun-ying Wang; Yong-hui Gao; Li-na Qiao; Jian-liang Zhang; Cheng-Li; Ya-xia Yan; Shu-ping Chen; Jun-ling Liu (BMC, 2018)
Abstract Background Cumulated evidence reveals that glial cells in the spinal cord play an important role in the development of chronic neuropathic pain and are also complicated in the analgesic effect of EA intervention. But the roles of microgliacytes and astrocytes of spinal cord in the process of EA analgesia remain unknown. Methods A total of 120 male Wistar rats were used in the present study. The neuropathic pain model was established by chronic constrictive injury (CCI) of the sciatic nerve. The rats were randomly divided into sham group, CCI group, and sham CCI + EA group, and CCI + EA group. EA was applied to bilateral Zusanli (ST36)-Yanlingquan (GB34). The mechanical (both time and force responses) and thermal pain thresholds (PTs) of the bilateral hind-paws were measured. The number of microgliacytes and activity of astrocytes in the dorsal horns (DHs) of lumbar spinal cord (L4-5) were examined by immunofluorescence staining, and the expression of glial fibrillary acidic protein (GFAP) protein was detected by western blot. Results Following CCI, both mechanical and thermal PTs of the ipsilateral hind-paw were significantly decreased beginning from the 3rd day after surgery (P < 0.05), and the mechanical PT of the contralateral hind-paw was considerably decreased from the 6th day on after surgery (P < 0.05). CCI also significantly upregulated the number of Iba-1 labeled microgliacytes and the fluorescence intensity of glial fibrillary acidic protein (GFAP) -labeled astrocyte in the superficial laminae of DHs on bilateral sides (P < 0.05). After repeated EA, the mechanical and thermal PTs at bilateral hind-paws were significantly relieved (P < 0.05). The increased of number of microgliacytes was markedly suppressed by 2 days' EA intervention, and the average fluorescence intensity was suppressed by 2 weeks' EA. The expression of GFAP protein were down-regulated by 1 and 2 weeks' EA treatment, respectively (P < 0.05). Conclusions Repeated EA can relieve neuropathic pain and mirror-image pain in chronic neuropathic pain rats, which is probably associated with its effect in downregulating glial cell activation of the lumbar spinal cord, the microgliacyte first and astrocyte later.